Tessellation Methods for Modeling the Material Structure - Burtseva L.; Werner F.; Valdes B.; Pestryakov A. N. Aleksey Nikolaevich; Romero R.; Petranovskii V. (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen